International financial management - Eun, Cheol S.; Resnick, Bruce G. (Boston : McGrow-Hill, 2007)
Business
Keywords: Financial management; Globalization; Multinational firm; The foreign exchange market; World financial market; International money systems; Corporate governance; International banking; International portfolio investment; Multinational cash management; International tax environment